2023
DOI: 10.33094/ijaefa.v15i2.820
|View full text |Cite
|
Sign up to set email alerts
|

Assessing total quality management and its impact on product quality: A cross-sectional study on textile industries in Bandung, Indonesia

Abstract: This study aims to predict the total quality management in medium to low-income companies in the textile industry in Bandung, Indonesia. The implementation of total quality management is one of the company's essential requirements. Previous studies indicate that the practice of quality management can improve the organizational performance in textile industry. We conducted a cross sectional survey study. The data is taken from the employees of textile industry. We made predictions using a non-parametric approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to Sarifuddin (2017), product quality enhances a company's reputation. Manik et al (2023) proposed that management's proactive engagement in quality improvement planning will increase product quality, which is advantageous for the firm. Based on these findings, the following theory is proposed:…”
Section: The Relationship Between Product Quality Customer Value and ...mentioning
confidence: 99%
“…According to Sarifuddin (2017), product quality enhances a company's reputation. Manik et al (2023) proposed that management's proactive engagement in quality improvement planning will increase product quality, which is advantageous for the firm. Based on these findings, the following theory is proposed:…”
Section: The Relationship Between Product Quality Customer Value and ...mentioning
confidence: 99%
“…Organizations also need to strengthen the culture of creativity and innovation within the organization by creating idea incubator programs and incentives for employees who contribute to improving services. (Manik et al, 2023) It can encourage employee flexibility in handling role changes by providing opportunities to develop new skills through regular job rotation. The organization's expectations for employees are to adapt quickly to changing times while continuing to prioritize the interests of society in every policy and service provided.…”
Section: Introductionmentioning
confidence: 99%
“…However, the employees' lack of motivation to improve their performance contributes to the current state of affairs being less than ideal. (Manik et al, 2023) The suspected cause of suboptimal employee performance is attributed to employees exhibiting a lack of discipline in their tasks and relatively high absenteeism rates. (Asif et al, 2019) The observed decline in employee work discipline suggests that certain employees may need to achieve optimal levels of work motivation.…”
Section: Introductionmentioning
confidence: 99%